The tiger : a true story of vengeance and survival - Vaillant, John (New York : Alfred A. Knopf, 2010)
Documents the efforts of a tiger conservation leader who was forced to hunt a man-eating tiger through the brutal Siberian winter, an effort that familiarized him with the creature's history, motives and unique method of attack.
"A Borzoi Book."
Includes bibliographical references (p. [321]-329).
Keywords: Tiger hunting -- Russia -- Russian far east; Tiger attacks -- Russia -- Russian far east; Tiger hunting -- Russian Far East (Russia); Animal attacks